Variation of moisture content and density in bamboo (gigantochloa scortechinii) : Effects of age and culm height / Abd. Jalil Ahmad, Jamaludin Kasim and Abd. Latif Mohmod - Ahmad, Abd. Jalil; Kasim, Jamaludin; Mohmod, Abd. Latif (Universiti Teknologi MARA Cawangan Pahang, 2000)
From the study it was observed that three-year-old bamboo had the highest mean density (0.75 g/cm3) and lowest mean initial moisture content (72.58%). Regardless of bamboo age, the top portion of the bamboo culm had the highest mean density and lowest mean initial moisture content. Initial moisture content was observed to decrease while oven dry density increased significantly with age and culm portion. Since three-year-old bamboo had the highest density and better qualities it should be selected and use for processing into bamboo products.